Sparse evidence of MERS‐CoV infection among animal workers living in Southern Saudi Arabia during 2012. Issue 2 (3rd December 2014) - Memish, Ziad A.; Alsahly, Ahmad; Masri, Malak al; Heil, Gary L.; Anderson, Benjamin D.; Peiris, Malik; Khan, Salah Uddin; Gray, Gregory C.
<x xml:space="preserve">Abstract</x> Middle East respiratory syndrome coronavirus (MERS‐CoV) is an emerging viral pathogen that primarily causes respiratory illness. We conducted a seroprevalence study of banked human serum samples collected in 2012 from Southern Saudi Arabia. Sera from 300 animal workers (17% with daily camel exposure) and 50 non‐animal‐exposed controls were examined for serological evidence of MERS‐CoV infection by a pseudoparticle MERS‐CoV spike protein neutralization assay. None of the sera reproducibly neutralized the MERS‐CoV‐pseudotyped lentiviral vector. These data suggest that serological evidence of zoonotic transmission of MERS‐CoV was not common among animal workers in Southern Saudi Arabia during July 2012.